In vitro Propagation of Globba schomburgkii Hook. f. via Bulbil Explants - SAENSOUK, Piyaporn; SAENSOUK, Surapon; PIMMUEN, Phattaraporn (Walailak Journal of Science and Technology (WJST), 2017)
An efficient and rapid protocol for the micropropagation of Globba schomburgkii Hook. f. via bulbil explants was investigated. The long divided and undivided bubils of G. schomburgkii Hook. f. were cultured on MS medium (Murashige and Skoog) that had either 3 mg/l benzyladenine (BA) or 0.5 mg/l naphthaleneacetic acid (NAA) added for 8 weeks. The results indicated that the long divided bulbils of G. schomburgkii Hook. f. showed a greater amount of plant regeneration than the undivided bulbils. Callus induction, as well as shoot and root formation, were observed when culturing microshoots of 1 cm in length on media (MS) that had Thidiazuron (TDZ) or NAA plus BA added at a range of concentrations for 8 weeks. The highest percentage of callus induction was 40 % when culturing the microshoots on MS medium supplemented with NAA and BA. The best result for shoot formation was achieved when culturing the microshoots on MS medium with TDZ added. The highest number of roots was obtained when culturing the microshoots on MS medium with NAA and BA added. The in vitro-derived plantlets of G. schomburgkii Hook. f. were transplanted to pots containing different types of potting mixture in a greenhouse. The survival rates were 80 % when G. schomburgkii Hook. f. was transplanted to sand.